An innovative method of applying fluxes using the low-pressure cold gas spraying method - Tomasz Wojdat (Przegląd Spawalnictwa, 2019)
In the paper, the results of tests of flux application for aluminum brazing processes using the low-presure cold gas spraying method, are presented. It was pointed out that this method could be used as an alternative to current methods of flux application, among others in the production of aluminum heat exchangers. The results of wettability tests made with braze spreading method on fluxed substrates and metallographic investigations of brazed joints are presented. Good quality of brazed joints without incompatibilities and good mechanical properties have been demonstrated.